2017
DOI: 10.3889/oamjms.2017.171
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Barriers and Motivators to Weight-Loss among Saudi People with Overweight or Obesity in Qassim Region - A Qualitative Study

Abstract: BACKGROUND:Obesity has become a global health threat. Saudi Arabia ranks among the countries with high obesity and overweight rates. This study aims to explore experiences of Saudi people with overweight or obesity with a particular focus on the perceived barriers and motivators to weight loss.MATERIAL AND METHODS:We used a qualitative approach to recruiting a purposive sample using maximum variation sampling technique. Those who had previously attempted weight loss at least once were included in the study. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 33 publications
3
16
1
Order By: Relevance
“…Improving physical health and body image were the two biggest drivers for males with obesity seeking MWM in Al-Mohaimeed's mixed-gender study. 5 Patients described being motivated to seek MWM by improving quality of life, and in particular, by their increasing loss of independence, which supports our study findings. 5 Two mixed-gender studies noted that functionality was a motivator for participants with obesity and severe obesity pursuing bariatric surgery.…”
Section: Motivations Of Males With Severe Obesitysupporting
confidence: 88%
See 3 more Smart Citations
“…Improving physical health and body image were the two biggest drivers for males with obesity seeking MWM in Al-Mohaimeed's mixed-gender study. 5 Patients described being motivated to seek MWM by improving quality of life, and in particular, by their increasing loss of independence, which supports our study findings. 5 Two mixed-gender studies noted that functionality was a motivator for participants with obesity and severe obesity pursuing bariatric surgery.…”
Section: Motivations Of Males With Severe Obesitysupporting
confidence: 88%
“…5 Patients described being motivated to seek MWM by improving quality of life, and in particular, by their increasing loss of independence, which supports our study findings. 5 Two mixed-gender studies noted that functionality was a motivator for participants with obesity and severe obesity pursuing bariatric surgery. 8,9 In particular, Wee found that males were motivated by poor physical functioning.…”
Section: Motivations Of Males With Severe Obesitysupporting
confidence: 88%
See 2 more Smart Citations
“…The challenges in losing weight are influenced by several issues at differing levels of the socio-ecological model. At the individual level, the list of barriers to weight management and sustainability includes low nutrition knowledge and skills (Ali, Baynouna & Bernsen, 2010), low motivation (Al-Mohaimeed & Elmannan, 2017;Metzgar et al, 2014;Abolhassani et al, 2012;Befort et al, 2008) and health problems (Abolhassani et al, 2012;Metzgar et al, 2014;Ali et al, 2010). At the interpersonal level, the biggest challenges are lack of family support (Al-Mohaimeed & Elmannan, 2017;Abolhassani et al, 2012;Metzgar et al, 2014) and competing demands, especially lacking the time for child care (Ali et al, 2010).…”
Section: Literature Review Definition and Concepts Of Weight Loss Chamentioning
confidence: 99%